2015
DOI: 10.1590/1519-6984.08014
|View full text |Cite
|
Sign up to set email alerts
|

Paecilomyces niveus Stolk & Samson, 1971 (Ascomycota: Thermoascaceae) as a pathogen of Nasonovia ribisnigri (Mosley, 1841) (Hemiptera, Aphididae) in Brazil

Abstract: Nasonovia ribisnigri is a key pest of lettuce (Lactuca sativa L.) in Brazil that requires alternative control methods to synthetic pesticides. We report, for the first time, the occurrence of Paecilomyces niveus as an entomopathogen of the aphid Nasonovia ribisnigri in Pinhais, Paraná, Brazil. Samples of mummified aphids were collected from lettuce crops. The fungus P. niveus (PaePR) was isolated from the insect bodies and identified by macro and micromorphology. The species was confirmed by sequencing Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Maharachchikumbura et al (2015) agreed with this familial placement. Zawadneak et al (2015) confirmed the placement of this genus in Thermoascaceae. Crous et al (2013a) …”
Section: Catenulomyces Egidi and De Hoogsupporting
confidence: 72%
“…Maharachchikumbura et al (2015) agreed with this familial placement. Zawadneak et al (2015) confirmed the placement of this genus in Thermoascaceae. Crous et al (2013a) …”
Section: Catenulomyces Egidi and De Hoogsupporting
confidence: 72%
“…P. lilacinus is widely used in the biological control of diseases in plants cultivated under field conditions (Veja et al, 2008). Other studies performed with this species reported mortality in nymphs of Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) (Fiedler and Sosnowska, 2007) and showed a potential in the control of Nasonovia ribisnigri (Mosley, 1841) (Hemiptera, Aphididae) a pest of lettuce (Lactuca sativa L.) in Brazil (Zawadneak et., al. 2015b) and its applicability in the control of nematodes of the genus Meloidogyne sp.…”
Section: Discussionmentioning
confidence: 99%
“…and bean (Phaseolus vulgaris L.) (Jones, 1994;Leckie, 2002;Ownley et al, 2004;Posada and Vega, 2005;Quesada-Moraga et al, 2006;Akello et al, 2007;Zawadneak et al, 2015b;Parsa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Isarioidea contains mesophiles, including several well-known entomopathogenic or nematophagous species, such as Paecilomyces lilacinus and P. javanicus (Samson, 1974;Kepenekci et al, 2015). Paecilomyces lilacinus is a soil fungus and has been used as an efficient and common nematicide (Kiewnick and Sikora, 2006;Siddiqui and Futai, 2009;Kepenekci et al, 2015), and also as a controller of greenhouse insects and mite pests (Fiedler and Sosnowska, 2007;Wraigt et al, 2000;Zawadneak et al, 2015). To date, no comparison of the efficacy of different P. lilacinus and P. javanicus isolates against diamondback moth (Pl.…”
Section: In Vitro Pathogenicity Of Paecilomyses To Pl Xylostella Andmentioning
confidence: 99%